Roll of thunder, hear my cry eaudiobook - Taylor, Mildred D. (Logan Family Saga, 2005)
Mildred D. Taylor's Newbery Award-winning masterpiece with an introduction written and read by Jacqueline Woodson, just in time for its 40th Anniversary!  Set in Mississippi at the height of the Depression, this is the story of one family's struggle to maintain their integrity, pride, and independence in the face of racism and social injustice. And it is also Cassie's story—Cassie Logan, an independent girl who discovers over the course of an important year why having land of their own is so crucial to the Logan family, even as she learns to draw strength from her own sense of dignity and self-respect.